Customer Satisfaction Performance Evaluation at PT PLN (Persero) West Java Using the Malcolm Baldrige Criteria for Performance Excellence - Ratih Siti Rachmawati; Dermawan Wibisono (Studi Akuntansi dan Bisnis Indonesia, 2025)
Purpose: This study assesses the application of the Malcolm Baldrige Criteria for Performance Excellence (MBCfPE) in PT PLN (Persero) West Java, focusing on Customer Focus to determine alignment with customer needs. Methodology/approach: Using a mixed-methods approach, data were collected through interviews, document reviews, and surveys of 97 employees involved in customer service. Pearson’s correlation confirmed questionnaire validity. Results/findings: PLN West Java effectively implements MBCfPE Customer Focus criteria, with an average satisfaction score of 8.94/10. Strengths include systematic complaint handling, customer engagement, and satisfaction evaluation. Gaps remain in optimizing data use, competitor benchmarking, and structured feedback analysis. Conclusions: Enhancing MBCfPE Customer Focus boosts satisfaction, loyalty, and retention, driving operational excellence and growth, with improvements in CRM, survey reach, and feedback use recommended. Limitations: The scope is limited to Customer Focus, excluding other MBCfPE criteria. Contribution: This study offers practical insights into implementing MBCfPE in the electricity sector, highlighting data-driven strategies to improve customer relationships and long-term performance.